FCRL3 promoter 169 CC homozygosity is associated with susceptibility to rheumatoid arthritis in Dutch Caucasians. Issue 6 (19th December 2006) - Thabet, Mohamed M; Wesoly, J; Slagboom, P E; Toes, R E M; Huizinga, T W J
Abstract : Background: Human leucocyte antigen is the only genetic risk factor for rheumatoid arthritis (RA) that has been consistently observed in different populations. A number of other genes such as PTPN22 and PADI4 showed population-specific association with RA susceptibility. Recently, Fc receptor-like 3 (FCRL3) gene was found to be associated with RA susceptibility in Japanese, but with conflicting results in other populations. Objective: To investigate the association of FCRL3 polymorphism with RA susceptibility and severity in Dutch Caucasian patients with RA, as well as to perform a meta-analysis to reveal the contribution of this gene to RA susceptibility. Methods: A total of 931 Dutch RA cases and 570 unrelated Dutch controls were genotyped for four FCRL3 single-nucleotide polymorphisms (SNPs). Genotyping was performed using the MassArray matrix-assisted laser desorption ionisation-time-of-flight mass spectrometry. Association of the FCRL3 SNPs with susceptibility to RA was examined by single-marker, carrier and haplotype analysis. Results: Carrier analysis of the SNP (rs7528684) revealed the association of CC genotype with a higher risk of developing RA as compared with TT and TC carriers (p = 0.039 and OR = 1.31). There was no significant difference in the genotype and allele frequencies of all investigated SNPs between cases and controls. Meta-analysis of all studies comparing 9467 individuals showed that the OR for the CC genotype to develop RA was 1.2 and the p value <0.001. Conclusion: A promoter polymorphism of FCRL3 (rs7528684) is associated with an increased risk of developing RA in Dutch Caucasians, suggesting that this association is relevant for RA in both Japanese and Caucasian populations.